HUBUNGAN INDEKS MASSA TUBUH DAN RIWAYAT KELUARGA DENGAN KEJADIAN DIABETES MELLITUS TIPE 2 DI DAERAH PESISIR KOTA KENDARI - en, Ti; Musyarrafah, Musyarrafah; Noor Kholidha, Andi; Aritrina, Pranita; Amal Abdal, Ikhlasul; wati, Arimas (Fakultas Kedokteran Universitas Islam Al-Azhar, 2019)
Background: Diabetes Mellitus is a metabolic disease characterized by chronic hiperglikemia and caused by the impairment of insulin secretion or insulin resistance or both. There are some risk factors in the process. They are obesity, lack of activity, nutritional deficiency, family history of diabetes, history of gestational diabetes, old age, and genetic. Research Purpose: This research purpose is to understand the relationship between risk factors including obesity and family history with the incident of type-2 DM in coastal area of Kendari. Research Methods: This research used analytical-observational study with case control approach. The independent variables used in this research are Body Mass Index (BMI) and family history while the the dependent variables are the incident of type-2 DM. The location of this research is working area of Puskesmas Mata, Puskesmas Benu-benua, Puskesmas Kandai, Puskesmas Abeli and Puskesmas Poasia located in the coastal area. There are 75 people choosen to be our samples by include and exclude criteria with cluster sampling method. Data are obtained by using questionnaire and laboratory analysis. The results are processed by applying Chi-Square test with p<0,050 and the Odd Ratio score. Research Result: This research showed that between BMI with the incident of type-2 DM has p=0,000 (OR=7,875), between family history with the incident of type-2 DM has p=0,030 (OR=2,800), between BMI and family history with the incident of type-2 DM has p=0,000 (OR=14,571). Conclusion: The conclusion of this research was that the relationship between BMI with the incident of type-2 DM in the coastal area of Kendari exists. The relationship between family history with the incident of type-2 DM in the coastal area of Kendari exists. The relationship between BMI and family history with the incident of type-2 DM in the coastal area of Kendari exists.